Effect of exercise on lipid peroxidation in student soccer players - Desty Ervira Puspaningtyas; Yuni Afriani; Silvi Lailatul Mahfida; Wara Kushartanti; Arta Farmawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Training is conducted to improve physiological functions that can support improvementof cardio-respiratory function (O2max). However, intensive training can lead to oxidativestress, which can contribute to health problems. The purpose of this study was to evaluatethe effect of training on serum lipid peroxidation levels in student soccer players. Thestudy was pre-experimental study with a one-shot case design conducted in April 2014.Twelve student soccer players from UGM who chosen by purposive sampling and metthe inclusion and exclusion criteria were involved in the study. Each subject receivedtraining in the form of O2max measurements using the yo-yo intermittent recovery test.Plasma malondialdehyde (MDA) levels were measured using the thiobarbituric acidmethod 30 min after O2max measurement. Pearson correlation was used to analyzethe correlation between O2max and plasma MDA levels. The mean age of subject was19.25±1.06 years old. Subjects had normal nutritional status (body mass index 20.99± 1.65) with mean body weight of 58.13±3.76 kg and mean height of 166.2±3.40cm. The mean O2max score was 49.56±0.61 mL/kg/min. The mean plasma MDA levelwas 4.32±2.09 μmol/L. There was no significant correlation between O2max and plasmaMDA levels (p=0.7717). In conclusion, training does not negatively impact oxidativestress conditions in student soccer players.